Wildfowl at risk, 1993 - Callaghan, Derek A; Green, Andy J (Wildfowl, 1993)
Complete reviews are given of the status of 25 wildfowl taxa (Anseriformes) thought to be candidates for globally threatened status, along with brief updates on me status of 40 taxa that were reviewed in detail in the previous issue of WILDFOWL. Each taxon is assigned a provisional category of threat in line with recent proposals for the re-evaluation of IUCN categories made by Mace and Lande (1991).